A revision of the genus Aelocampsomeris Bradley, 1957 (Hymenoptera: Scoliidae: Scoliinae) - Castagnet, Jean-Baptiste; Noll, Fernando Barbosa [UNESP]; Golfetti, Ivan Fernandes [UNESP] (FapUNIFESP (SciELO), 2025)
Abstract Scoliidae is a family commonly found throughout the globe and, currently, one of the most neglected taxa within the Hymenoptera. As expected, information about this group is extremely scarce, confusing, and outdated, especially when it comes to its taxonomy and systematics. Therefore, here the genus Aelocampsomeris Bradley, 1957 is revised. This genus comprises three species: Aelocampsomeris brethesi Bradley, 1927, Aelocampsomeris campestris Burmeister, 1854, and Aelocampsomeris variegata Fabricius, 1793. While Aelocampsomeris variegata, is a very common and well-known species, Aelocampsomeris brethesi, and Aelocampsomeris campestris, remain much less known. Examination of the male and female type specimens, as well as new specimens, allowed an accurate review. We provide a detailed morphological redescription, illustrations and a species key.